The impact of cash flows and earnings on dividend : evidence from Southeast Asia countries / Khairul Anuar Kamardin, Mohd Shatari Abdul Ghafar and Wan Adibah Wan Ismail - Kamardin, Khairul Anuar; Abdul Ghafar, Mohd Shatari; Wan Ismail, Wan Adibah (Institute of Research, Development and Commercialization (IRDC), 2006)
The purpose of this research is to examine the impact of cash flows and earnings in setting the dividend policy in Malaysia, Singapore, Indonesia, Thailand and the Philippines. A total of JJ3J companies from the years 200 J-2003 were tested in this research. The research found that about 38 percent of the sample reported either losses reduced or omitted dividends. In contrast, only 35 percent of the J066 companies did not report losses reduced or omitted dividends. The results found that changes of earnings is significantly associated with dividend changesfor all sample companies. However, the research found that the level of cash flows is not significant in explaining the dividend changes in Malaysia, Singapore, Indonesia, Thailand and the Philippines. On the other hand, the cashflows arefound to be significant in explaining the dividend change in all current operaling earnings and cash flows are found to have information content in predicting future earnings for all the sample companies. However, this research can only give earnings in Thailand and not in other countries.